1981
DOI: 10.1093/infdis/144.6.499
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of C3 by Neutral Proteases from Granulocytes in Pleural Empyema

Abstract: The possibility of direct inactivation of C3 by granular enzymes from polymorphonuclear leukocytes (PMNLs) in pleural empyema was examined. As a group, pleural empyema from 10 patients with purulent effusions and a positive bacteriologic culture cleaved significantly more 125I-labeled C3 bound to Sepharose (18.4070 ± 7.3070) than did 19 sterile pleural effusions (2.4070 ± 0.9070; P« 0.001) and sonicates from bacterial strains commonly found in empyema (1.4070 ± 0.2070). Granular enzymes from 7 x 10 6 PMNLs cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1
1

Year Published

1982
1982
1993
1993

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 23 publications
1
14
1
1
Order By: Relevance
“…Either decreased opsonization of S. aureus might be a consequence of the imbalance between the rate of coating of bacteria with functionally active C3 and the logarithmic growth of the organisms, or cleavage of the opsonically active factor by fJ-I-H-globulin, C3b inactivator, and proteases [47][48][49][50][51] could have occurred during the development of a purulent infection. Loss of opsonic activity, as well as proteolytic cleavage of C3, has been recently demonstrated in several exudates rich in PMNLs [13,15,24]. Finally, our experiments showed that PMNLs attracted into the infected tissue cages displayed normal phagocytic bactericidal function, a finding which is apparently in contradiction with our observations in sterile tissue cages.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Either decreased opsonization of S. aureus might be a consequence of the imbalance between the rate of coating of bacteria with functionally active C3 and the logarithmic growth of the organisms, or cleavage of the opsonically active factor by fJ-I-H-globulin, C3b inactivator, and proteases [47][48][49][50][51] could have occurred during the development of a purulent infection. Loss of opsonic activity, as well as proteolytic cleavage of C3, has been recently demonstrated in several exudates rich in PMNLs [13,15,24]. Finally, our experiments showed that PMNLs attracted into the infected tissue cages displayed normal phagocytic bactericidal function, a finding which is apparently in contradiction with our observations in sterile tissue cages.…”
Section: Discussioncontrasting
confidence: 94%
“…Although polymorphonuclear leukocytes (PMNLs) accumulating around a foreign body appear microscopically normal, their functional status as well as the opsonizing capacity of the surrounding fluid have never been explored because of the lack of an appropriate animal model. In the present communication we describe the development of an animal model that reproduces the clinical characteristics of a foreign body infection and thus allows the in vitro evaluation of the various phagocytic steps in its neighborhood [13][14][15][16].…”
mentioning
confidence: 99%
“…Bronchial lavage fluid was obtained from six patients by bronchoscopy on the same day that the sputum samples were obtained. Pathogens isolated from sputum included: Haemophilus influenzae [18], Streptococcus pneumoniae [8], Escherichia coli [1], Proteus vulgaris [1], S aureus [5], and Aspergillus [1]. Three patients had mixed infections.…”
Section: Methodsmentioning
confidence: 99%
“…Granular enzymes were prepared from PMNs collected from fresh heparinized blood of normal adult volunteers, according to the method of Baggiolini [21] and modified as previously described [8]. They had an elastolytic activity of 17.4 UE and granulocyte elastase-like activity of 0.59 UTGP (see below for definition of units).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation